The Impact of Holy Kaaba Cubic Shape on The Incorporeal Space - Alhawasli, Hiba; Bemanian, Mohammad Reza (Journal of Islamic Architecture, 2018)
The Holy Kaaba is the house of God; the home of greatness secrets, wisdom and divine beauty, which is reflected in all his creatures. This study aims to find the role of the shape of holy Kaaba in producing such kind of spaces and discovering the characteristics possessed by its form which has an impact in creating such incorporeal space. In this study, scientific articles and research were used to achieve the rules of research theory with taking into account considering the position of Islamic theoretical and practical wisdom. In the process of creating works of art, architecture and joint issues with urbanization, and by using the rational method to find out, in the end, the study shows the space of Holy Kaaba is a sign of divine glory from visualization and embodiment material. The nature veil in this space shines the divine light in human conscience. Human perception of space is related to his knowledge of himself and the world. Human in the use of space is approaches to percepts the true meaning of it. His intellectual device with a personal intelligent device that space is created will be compatible. The holy Kaaba spiritual space makes human feel poverty in front of the richness of the homeowner. Also, a sense of peace and sustainability due to a connection felt with God and seeking to reach the perfection that has been formed by the cube-shaped of holy Kaaba.